Reaction rate of radiative capture of proton by 11B nucleus - Dubovichenko, S.B.; Burkova, N.A.; Tkachenko, A.S.; Zazulin, D.M.; Akat, A.A. (Recent Contributions to Physics, 2024)
The 11B(p,γ)12C reaction is of considerable interest in the field of controlled thermonuclear fusion and in nuclear astrophysics. In thermonuclear reactors, structural elements containing boron can be used as neutron absorbers. This reaction is one of the reactions of 11B production in the starsю. The rate of the 11B(p,γ)12C reaction (occurring in the interiors of first-generation stars) can be of great importance for the amount of 11B and 10B observed today in the Earth's crust and in the interstellar medium. Therefore, in this work, within the framework of a modified potential cluster model with a classification of orbital states according to Young's diagrams and taking into account allowed and forbidden states, we examined the possibility of describing the available experimental data for the total cross sections of the radiative p11B capture to the ground state of the 12C nucleus at energies up to 1.5 MeV. It is shown that only on the basis of E1 and M1 transitions from the p11B scattering states, taking into account the first resonance for the ground state of the 12C nucleus, it is quite possible to explain the magnitude and shape of the experimental astrophysical S-factor. The work presents comparisons the astrophysical S-factors of the radiative p11B capture to the ground state of the 12C nucleus found by us with the experimental data available in the literature. Based on the obtained theoretical S-factor, the rate of this reaction was calculated in the temperature range from 0.01 to 1 T9. The calculated results for rates are approximated by a simple expression, which simplifies their use in applied thermonuclear and astrophysical research.